International congress on transposable elements (ICTE 2024) in Saint Malo: breaking down transposon waves and their impact - Pascale Lesage; Emilie Brasset; Gael Cristofari; Clément Gilbert; Didier Mazel; Rita Rebollo; Clémentine Vitte (Mobile DNA)
Abstract From April 20 to 23, 2024, three hundred ten researchers from around the world gathered in Saint-Malo, France, at the fourth International Congress on Transposable Elements (ICTE 2024), to present their most recent discoveries on transposable elements (TEs) and exchange ideas and methodologies. ICTE has been held every four years since 2008 (except in 2020, when it was exceptionally transformed into a seminar series due to the Covid-19 pandemic) and is organized by the French network on Mobile Genetic Elements (CNRS GDR 3546). This fourth edition offered two keynote presentations and four sessions presenting the latest findings and encouraging discussions on the following topics: (1) TEs, genome evolution and adaptation; (2) TEs in health and diseases; (3) TE control and epigenetics; (4) Transposition mechanisms and applications. The 2024 edition also included a half-day satellite workshop on new challenges in TE annotation, organized in collaboration with the TE Hub. The meeting gathered long-term TE enthusiasts, as well as newcomers to the field, with 77% of the participants attending ICTE for the first time.